Consumer heterogeneity and willingness to pay for common reed insulation board : a choice experiment approach - Häyrinen, Liina; Tienhaara, Annika; Pouta, Eija (Elsevier, 2026)
The growing demand for sustainable construction materials and the need to restore marginal lands have created opportunities for innovative bio-based solutions. Common reed (Phragmites australis) offers both ecological benefits and potential as a renewable insulation material, particularly when cultivated on underutilised land. However, the commercial success of such novel materials depends on consumer acceptance and willingness to pay. This study examines consumer preferences and willingness to pay for insulation boards made from common reed using a discrete choice experiment conducted in Finland in 2024 (N = 2974). Respondents evaluated four insulation boards, namely cellulose wool, stone wool, wood fibre and reed fibre, based on five attributes: thermal insulation, domestic origin, fire safety, environmental friendliness and price. A latent class model identified five consumer segments. One segment (10.7%) displayed a clear preference for reed fibre boards, valuing thermal insulation and environmental benefits while being the least price-sensitive, suggesting higher stated valuation for the material. A younger age, female gender, a background in construction and positive views on the utilisation of marginal lands increased the likelihood of segment membership. While excellent thermal insulation and domestic origin were important across all groups, their relative importance varied. The findings highlight that a distinct group of consumers has a clear preference for reed fibre insulation, especially if marketed with a focus on sustainability and renewability. The study underscores the importance of targeted communication and policy support to facilitate the adoption of novel bio-based construction materials.
Keywords: bio-based insulation materials; reed fibre; sustainable construction; consumer preferences; discrete choice experiment; willingness to pay